Ownership Structure and Financial Sustainability Evidence from Com-mercial Banks in Nigeria with International Authorization - Livinus Nkuri Maimako; Ahmed Razman Abdul Latiff; Wan Fadzila Wan Yusoff (International Business and Accounting Research Journal, 2021)
Purpose The main purpose of this study is to determine the moderating role of managerial intention on the relationship between ownership structure (institutional ownership and family ownership) and the financial sustainability of commercial banks in Nigeria. It will also demonstrate the direct relationship between family ownership, institution ownership, and managerial intention on financial sustainability. Design/methodology/ approach The theoretical inside of this study is based on agency theory. family ownership and institutional are the dimensions of ownership structure while the percentage of the non-performing loan is used as a proxy for financial sustainability. The study analyzed 56 annual reports of deposit money banks in Nigeria for the period 2014-2020. Balanced panel data were collected for the analyses and fixed effect was used to test the relationship between the variables. Findings We found out that both family ownership and institutional ownership exert a significant positive effect on financial sustainability (percentage of non-performing) in Nigeria's deposit money bank. This suggests that an increase in family and institutional ownership will enhance monitoring and control of non-performing loans of commercial banks. It is also in agreement with agency theory that more concentration in ownership improves control and monitory. Practical implications The study contributes to the understanding of banks' financial sustainability link with a component of ownership structure (institutional ownership and family ownership). The result of the study will provide an insight for practitioners and policymakers on the need to prescribe corporate governance code on the financial sustainability of banks. Originality/ value This study is timely given the fact that deposit money banks are presently struggling with issues of financial sustainability as a result of the coronavirus pandemic., the is an extension of the work of ( Nkuri, Latiff,  & Yusoff, 2021) Which was conceptually published. The study is important to policymakers and practitioners to formulate policy that will merge rather than a takeover. family ownership should be encouraged to reduce agency problems.